Design Development of Food & Beverage Product Packaging for SMES co in Java and West Nusa Tenggara, Economic Corridor. - Agus Windharto (IPTEK Journal of Proceedings Series, 2014)
Population of Food & Beverage SME's Co in Indonesia reached 38 % of total 52 million SMEs, equivalent to 19.76 million SMEs. Indonesian Consumption reached Rp997 trillion in 2012 and its 27 % is in the form of processed foods that packed (Rp296, 19 trillion). Expenditure of industrial packaging products for SME are big, worth 5 % of whole packaging product price that equivalent to Rp13, 46 trillion. SMEs Contribution (21 % worth of 19.76 million) is still relatively considered small competitive to Indonesian market from those of medium and large industrial supply both for local and abroad (79 %). The main issue is Food & Beverage SMEs Competitiveness products relatively low, lack of promotion, weak brand, packaging design not meet good standards and food quality below safety standards. The purpose of this research is to improve the competitiveness of food and beverage SMEs Co through capacity building, took places on some "brands and packaging design center" in Java, Bali and Nusa Tenggara.  Developing branding design and planogram for consumer pack and transport pack packaging through research MP3EI 2012-2014 Participatory design research methods are preceded by informal discussions with SMEs to explore the problems, goals, and defining development strategies. This method expand further more by training programs in cooperate with IPF,  East Java Industry and Trade Ministry of Commerce, Indonesian Ministry of Trade. SME Product Packaging Design Competition between universities in East Java in 2011-2013 preceded by a workshop for students to produce a design that meets the standards and can be well used by SMEs. Other programs conducted in form of producing brand and packaging design SMEs in East Java and West Nusa Tenggara. The result of this research are increasing awareness of SMEs for good brand and packaging design, increasing student capacity -proven by winning in Asian Star 2011 and 2012 competition, obtaining 11 gold medals. Formulation of Product packaging coaching role models. Formulation of Standard Operating Procedure for branding and packaging and achieving efficiency for SME food product packaging supply through production sharing.